Changing face of adult coeliac disease: experience of a single university hospital in South Yorkshire. Issue 915 (1st January 2002) - Sanders, D S; Hurlstone, D P; Stokes, R O; Rashid, F; Milford-Ward, A; Hadjivassiliou, M; Lobo, A J
Abstract : Objective: To determine the incidence and presenting features of adult coeliac disease in a single university hospital in South Yorkshire. Design: A retrospective case finding study. Data were obtained from pathology and immunology databases, clinical notes, dietetic records, and patient questionnaires. Setting: Royal Hallamshire Hospital in South Yorkshire, England. Participants: All recorded cases of coeliac disease. Main outcome measures: Crude annual incidence rates for coeliac disease was obtained. The numbers of coeliac antibody profiles requested per year from the Royal Hallamshire Hospital were ascertained. Age at diagnosis, sex, year of diagnosis, presenting symptoms, associated conditions, and delay in diagnosis was documented. In addition the specialty of the clinician who made the diagnosis was noted. Results: There were 264 cases in total (male n=86, ratio 1:2). Mean age at diagnosis was 44.9 years (range 1–82, median 44.5). A trend was observed from 1990 to 2000 inclusive, of an annual increase in the incidence of coeliac disease. There has been a coincidental increase in the measurement of associated antibodies. Although 28.4% of patients presented with gastrointestinal symptoms, 20.1% had iron deficiency anaemia. The ratio of typical to atypical symptoms was 1:2.5. (single sample test of proportions p<0.001). The diagnosis was made by a gastroenterologist in only 52.7% of cases. The median duration of symptoms before the diagnosis of coeliac disease was 4.9 years (range 0.25–16 years). Conclusion: Coeliac disease is now presenting more commonly without gastrointestinal symptoms and often to specialties other than gastroenterology. Although more cases are diagnosed, this may be a reflection of increasing recognition rather than a true increase in incidence.